2010
DOI: 10.1002/jclp.20752
|View full text |Cite
|
Sign up to set email alerts
|

Coping Style

Abstract: The fit of patient coping style and psychotherapy focus has been suggested as improving treatment outcome. This article reviews the definitions, measures, and previous research surrounding this hypothesis. An original meta-analysis of 12 carefully selected studies (N = 1,291 patients) resulted in a weighted, mean effect size (d) of .55 in favor of a fit between externalizing patients and symptom-focused treatment or, alternatively, internalizing patients and insight-focused treatment. This medium-size effect i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…Past research has shown that interventions aimed at changing coping styles has improved health outcomes. 39 Consequently, consideration should be given to some form of education or intervention for these young adults aimed at increasing the problem-based strategies and minimizing emotion and avoidance based strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has shown that interventions aimed at changing coping styles has improved health outcomes. 39 Consequently, consideration should be given to some form of education or intervention for these young adults aimed at increasing the problem-based strategies and minimizing emotion and avoidance based strategies.…”
Section: Discussionmentioning
confidence: 99%
“…First, not all young people benefit from these more directive approaches (e.g., Birmaher et al, 2000), or are optimally matched to them. In particular, research with adult populations shows that some clients*particularly those who are more resistant, have more internalized coping styles, and do not want directive interventions (Beutler, Harwood, Kimpara, Verdirame, & Blau, 2011;Beutler, Harwood, Michelson, Song, & Holman, 2011;Swift, Callahan, & Vollmer, 2011)*may do better in nondirective approaches. Second, the focus of CBT interventions towards specific, diagnosed mental health problems means that they may not be appropriate*and have not been evidenced*for treating the full spectrum of psychological distress, which relates to the impact of external stressors on a person's lived experience, rather than dysfunctional cognitive or behavioral patterns.…”
mentioning
confidence: 97%
“…First, pooled evidence corroborated that perceived social support would optimize the coping ability of schizophrenia patients' primary caregivers against stress and adversity [7]. Coping styles including positive and negative coping style are de ned as the pattern of behavior that is predominantly adopted by individuals when encountering unexpected situations [8] and have been consistently con rmed to be associated with PTG in studies. For example, studies found that positive coping style was positively related to PTG in parents of children with autism [9,10] and parents of cerebral palsy children [11].…”
Section: Introductionmentioning
confidence: 93%